The Role of Blitard Police Satsamapta Precision Pioneer Patrol in the Prevention of Motor Vehicle Theft - Ananda, I Wayan Nugraha Satya (Advances in Police Science Research Journal, 2024)
Theft is a conventional crime that is widely committed by society. According to Book II of the Criminal Code, theft is included as a crime. The crime of theft as stated in Article 362 of the Criminal Code is defined as: taking goods, wholly or partly belonging to another person, with the aim of possessing them unlawfully. Based on data collected by the Blitar Police Criminal Investigation Unit, criminal acts of theft that occur in the jurisdiction of the Blitar Police are classified into five, including ordinary theft, aggravated theft, light theft, violent theft and motor vehicle theft. The National Police of the Republic of Indonesia has the task of ensuring the realization and maintenance of a public security situation and the protection of the Indonesian people from various security and social security disturbances as stated in Article 13 of Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia. This research examines the role of the Blitar Police Samapta Unit patrol unit to prevent motor vehicle theft in the Blitar Police Legal area in order to create a good and controlled situation and condition of security and public order.